2020
DOI: 10.15537/smj.2020.3.24915
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of waist-to-height ratio in identifying cardiovascular risk factors and metabolic syndrome among adult Saudis

Abstract: To evaluate the diagnostic performance of waist to height ratio (WHtR) to screen for cardiovascular risk factors (CVRF) and metabolic syndrome (MetS) among Saudis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Some Mexican scholars provided evidence that WHtR could predict the risk assessment of type 2 diabetes mellitus in Mexican population (36). In addition, Rasmieh Alzeidan emphasized that waist height ratio showed a good diagnostic performance for metabolic syndrome among Saudis (37). It should be noted that WC and its change, are more strongly associated with the risk of type 2 diabetes than BMI, and changes in body weight among Chinese adults, and it's essentially the same in our results (38).…”
Section: Discussionsupporting
confidence: 78%
“…Some Mexican scholars provided evidence that WHtR could predict the risk assessment of type 2 diabetes mellitus in Mexican population (36). In addition, Rasmieh Alzeidan emphasized that waist height ratio showed a good diagnostic performance for metabolic syndrome among Saudis (37). It should be noted that WC and its change, are more strongly associated with the risk of type 2 diabetes than BMI, and changes in body weight among Chinese adults, and it's essentially the same in our results (38).…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, it is necessary to explore and compare the predictive power of different obesity indicators on the risk of dyslipidemia simultaneously. Accumulating studies had been conducted to explore associations between different anthropometric obesity indices like BMI [ 13 , 14 , 15 ], WC [ 14 , 15 , 16 ], WHtR [ 16 , 17 , 18 ], and the risk of dyslipidemia. However, most of them were cross-sectional studies [ 13 , 15 , 16 , 17 , 18 ], which could not make causal association between obesity status and the dyslipidemia, and those findings were controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies had been conducted to explore associations between different anthropometric obesity indices like BMI [ 13 , 14 , 15 ], WC [ 14 , 15 , 16 ], WHtR [ 16 , 17 , 18 ], and the risk of dyslipidemia. However, most of them were cross-sectional studies [ 13 , 15 , 16 , 17 , 18 ], which could not make causal association between obesity status and the dyslipidemia, and those findings were controversial. Changes in anthropometric indices were better for assessing the effect of excess fat [ 19 ], and some longitudinal studies assessed possible impacts of long-term changes in anthropometric indices on the risk of incident dyslipidemia [ 2 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding was in line with cross-sectional studies conducted in Saudi Arabia, China, Brazil, and Jimma. 25 , 35 , 48 , 49 The possible reason for WHtR to be a better tool for screening hypertension could be due to its consideration of both height and WC of an individual. The height could affect the fat distribution; resulting in short people having a higher chance of accumulating fat centrally, and they also have a higher level of blood cholesterol and SBP than tall people.…”
Section: Discussionmentioning
confidence: 99%
“…This result agreed with cross-sectional studies conducted in Brazil, Saudi Arabia and Korea. 29 , 48 , 60 The decreased power of BMI to screen hypertension could be due to its incapability to differentiate fat mass and muscle mass which might lead to under screening of health risks. 21 This is supported by a result from the Britain study, which indicated that more than one in 7 normal weight males and more than one in 3 normal weight females could be at increased health risk according to their abdominal fat distribution.…”
Section: Discussionmentioning
confidence: 99%